2020
DOI: 10.1111/jcpe.13331
|View full text |Cite
|
Sign up to set email alerts
|

Hard and soft tissue alterations during the healing stage of immediate implant placement and provisionalization with or without connective tissue graft: A randomized clinical trial

Abstract: Immediate implant placement and provisionalization (IIPP) in the extraction socket is an attractive treatment modality that facilitates immediate tooth replacement and reduces treatment time, cost and surgical trauma as compared to delayed approaches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
79
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(98 citation statements)
references
References 28 publications
(44 reference statements)
6
79
0
13
Order By: Relevance
“…Thirty‐two of the included studies (Basler et al, 2018; Benic et al, 2017; Bertl et al, 2017; Bittner et al, 2020; Borges et al, 2020; Cabanes‐Gumbau et al, 2019; Canullo et al, 2018; Clementini et al, 2020; De Bruyckere et al, 2020; Eeckhout et al, 2020; Fischer et al, 2019; Friberg & Jemt, 2012; Galarraga‐Vinueza et al, 2020; Hinze et al, 2018; Hosseini et al, 2020; Huber et al, 2018; Jiang et al, 2020; Papi et al, 2020; Parvini et al, 2020; Rojo et al, 2018, 2020; Sanz Martin et al, 2016; Sanz‐Martin et al, 2019; Sapata et al, 2018; Schneider et al, 2011; Thoma et al, 2020; Tian et al, 2019; van Nimwegen et al, 2018; Wang et al, 2019; Wei et al, 2019; Wittneben et al, 2016; Zeltner et al, 2017) assessed volumetric changes with optical scanning‐based digital technologies. Among them, four studies also assessed mucosal thickness (MT) changes with transgingival piercing methods (Hosseini et al, 2020; Huber et al, 2018; Papi et al, 2020; Thoma et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty‐two of the included studies (Basler et al, 2018; Benic et al, 2017; Bertl et al, 2017; Bittner et al, 2020; Borges et al, 2020; Cabanes‐Gumbau et al, 2019; Canullo et al, 2018; Clementini et al, 2020; De Bruyckere et al, 2020; Eeckhout et al, 2020; Fischer et al, 2019; Friberg & Jemt, 2012; Galarraga‐Vinueza et al, 2020; Hinze et al, 2018; Hosseini et al, 2020; Huber et al, 2018; Jiang et al, 2020; Papi et al, 2020; Parvini et al, 2020; Rojo et al, 2018, 2020; Sanz Martin et al, 2016; Sanz‐Martin et al, 2019; Sapata et al, 2018; Schneider et al, 2011; Thoma et al, 2020; Tian et al, 2019; van Nimwegen et al, 2018; Wang et al, 2019; Wei et al, 2019; Wittneben et al, 2016; Zeltner et al, 2017) assessed volumetric changes with optical scanning‐based digital technologies. Among them, four studies also assessed mucosal thickness (MT) changes with transgingival piercing methods (Hosseini et al, 2020; Huber et al, 2018; Papi et al, 2020; Thoma et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies (Basler et al, 2018; Benic et al, 2017; Bittner et al, 2020; Canullo et al, 2018; Clementini et al, 2020; De Bruyckere et al, 2020; Eeckhout et al, 2020; Fischer et al, 2019; Friberg & Jemt, 2012; Hinze et al, 2018; Hosseini et al, 2020; Huber et al, 2018; Sanz Martin et al, 2016; Sanz‐Martin et al, 2019; Sapata et al, 2018; Schneider et al, 2011; Thoma et al, 2020; van Nimwegen et al, 2018; Wang et al, 2019; Wittneben et al, 2016; Zeltner et al, 2017) reported generating 3D digital models from constructed dental casts obtained with different impression materials (including silicone, alginate, polyether, and polyvinyl siloxane) with the use of desktop 3D optical scanners (indirect technique). The other eleven studies (Bertl et al, 2017; Borges et al, 2020; Cabanes‐Gumbau et al, 2019; Galarraga‐Vinueza et al, 2020; Jiang et al, 2020; Papi et al, 2020; Parvini et al, 2020; Rojo et al, 2018, 2020; Tian et al, 2019; Wei et al, 2019) had obtained the 3D digital models with the use of intra‐oral scanners (direct technique). Among them, six studies reported that a short‐span area was scanned (Galarraga‐Vinueza et al, 2020; Parvini et al, 2020; Rojo et al, 2018, 2020; Tian et al, 2019; Wei et al, 2019), while other articles did not provide information regarding the size of the scanned area.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations